IMPROVEMENT OF GEOPHONE SENSITIVITY AT LOWER FREQUENCY (1 to 8HZ) - Luka, Mawa Patrick (IRC, 2016)
Geophone is a device which measures ground movement by converting the detected motion into voltage. Geophones have been used in field of geology for many years especially for finding new source of oil and gas deposits. Geophones are made up of spring mounted magnetic mass moving back and forth in a wire coil to create voltage. The response of coil is proportional to the velocity of the ground motion. At various frequencies seismic events can be measures using geophones. However most geophones only allow accurate measurements above their natural frequency (5Hz), below this range geophones encounter inaccuracy detecting the motion.